Pilot Study Measuring the Novel Satiety Hormone, Pro-Uroguanylin, in Adolescents With and Without Obesity. Issue 3 (March 2018) - Di Guglielmo, Matthew D.; Tonb, Dalal; He, Zhaoping; Adeyemi, Adebowale; van Golen, Kenneth L.
ABSTRACT: Objective: Disruption of satiety signaling may lead to increased caloric intake and obesity. Uroguanylin, the intestinal hormone, travels as a precursor to the central nervous system where it activates guanylyl cyclase C and stimulates pro-satiety neurons. Rodent studies have demonstrated that guanylyl cyclase C-knockout mice overeat and have increased weight gain versus wild-type mice and hyper-caloric obesity diminishes uroguanylin expression. We measured circulating plasma pro-uroguanylin, along with other gastrointestinal peptides and inflammatory markers, in human adolescents with and without obesity, as a pilot study. We hypothesized that adolescents with obesity would have less circulating pro-uroguanylin than adolescents without obesity have. Methods: We recruited 24 adolescents (age 14–17 years) with and without obesity (body mass index >95% or body mass index <95%) and measured plasma pro-uroguanylin at fasting and successive time points after a meal. We measured 3 other satiety hormones and 2 inflammatory markers to characterize overall satiety signaling and highlight any link between uroguanylin and inflammation. Results: Female adolescents with obesity had lower circulating pro-uroguanylin levels than female adolescents without obesity; we observed no difference in males. Other measured gastrointestinal peptides varied in their differences between cohorts. Inflammatory markers were higher in female participants with obesity. Conclusions: In adolescents with and without obesity, we can measure circulating pro-uroguanylin levels. In female adolescents without obesity, levels are particularly higher. Pro-uroguanylin secretion patterns differ from other circulating gastrointestinal peptides. In female adolescents with obesity, inflammation correlates with decreased pro-uroguanylin levels. Abstract : Supplemental Digital Content is available in the text